Banaras jyotirliṅgas: constitution and transformations of a transposed divine group and its pilgrimage - Lazzaretti, Vera (Kervan, 2013)
Banaras (Varanasi, Uttar Pradesh, India) is renowned as one of the more notable pilgrimage destinations of India. The ways of approaching and investigating the sacred landscape and the religious practices of this city varied throughout times and are still a matter of discussion among scholars. The author firstly addresses this debate in order to re-conceptualize the need and intents of writing (still) about Banaras and its mainstream religious traditions. The contribution addresses one common pattern of Indian sacred geography, that is the spatial transposition of gods. The article, in fact, goes through the formation path of a transposed group of pan-Indian deities, namely the jyotirliṅgas, in a city which is presented by eulogistic literature as a universal tīrtha, where all sacred centres and gods dwell. Through the analysis of textual and visual material the author shows how these divine forms have been produced in the city’s territory throughout time and projected spatially in the various shrines and, eventually, in a procession. The pilgrimage circuit connected with the twelve local jyotirliṅgas is investigated as a recent and evolving practice of Banaras religious life and its currently deviating path is shown as something to be constantly rephrased and negotiated. Ritual transformations appear as challenged by the need to adapt and survive in a developing urban context, where sacred space is shared, contested and cyclically re-written.